2014
DOI: 10.1080/00223131.2014.907550
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gamma radiolysis on pit initiation of zircaloy-2 in water containing sea salt

Abstract: In spent fuel pools at the Fukushima Daiichi Nuclear Power Station (1F), seawater was injected for cooling purposes after the tsunami disaster in March 2011. It is well known that the chloride in the seawater has the potential to cause localized corrosion (e.g., pitting corrosion) in metals. In this study, we evaluated the pitting potentials of zircaloy-2, the material used in the fuel cladding tubes in 1F, as a function of chloride concentration. To accomplish this, we used artificial seawater under gamma-ray… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…According to a previous study, at several mol·dm −3 Cl − and high absorbed dose, the only long-lived product originating from NaCl is ClO 3 − (concentration in the order of 10 −3 mol·dm −3 ) and HClO and ClO 2 − concentrations were near the detection limit (10 −5 mol·dm −3 ) [4]. A simulated seawater experiment at room temperature also showed that no Cl − and Br − induced products were found after a 100 h irradiation at 5 kGy h −1 [11]. In this study, since the concentration of Cl − was much lower than in this report, radiolytic products originating from seawater components in the autoclave were negligible compared to the considerable amounts of Cl − which are present in seawater.…”
Section: Product Analysis Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…According to a previous study, at several mol·dm −3 Cl − and high absorbed dose, the only long-lived product originating from NaCl is ClO 3 − (concentration in the order of 10 −3 mol·dm −3 ) and HClO and ClO 2 − concentrations were near the detection limit (10 −5 mol·dm −3 ) [4]. A simulated seawater experiment at room temperature also showed that no Cl − and Br − induced products were found after a 100 h irradiation at 5 kGy h −1 [11]. In this study, since the concentration of Cl − was much lower than in this report, radiolytic products originating from seawater components in the autoclave were negligible compared to the considerable amounts of Cl − which are present in seawater.…”
Section: Product Analysis Resultsmentioning
confidence: 96%
“…Venkateswaran [10] reported that galvanically decoupled zircaloy-2 without irradiation will not undergo pitting attack. Also, Motooka et al [11] reported that Cl − was the main aggressive species and oxide formation was promoted by irradiation in the pitting test for zircaloy-2 in simulated seawater at room temperature. However, both these studies were conducted at lower temperatures and without the galvanic coupling which actual fuel assemblies have.…”
Section: Introductionmentioning
confidence: 98%